Targeting therapeutic vulnerabilities with PARP inhibition and radiation in IDH-mutant gliomas and cholangiocarcinomas - Wang, Yuxiang; Wild, Aaron T.; Turcan, S̨evin; Wu, Wei H.; Sigel, Carlie; Klimstra, David S.; Ma, Xiaoxiao; Gong, Yongxing; Holland, Eric C.; Huse, Jason T.; Chan, Timothy A. (Science advances, 2020)
Mutations in isocitrate dehydrogenase (IDH) genes occur in multiple cancer types, lead to global changes in the epigenome, and drive tumorigenesis. Yet, effective strategies targeting solid tumors harboring IDH mutations remain elusive. Here, we demonstrate that IDH-mutant gliomas and cholangiocarcinomas display elevated DNA damage. Using multiple in vitro and preclinical animal models of glioma and cholangiocarcinoma, we developed treatment strategies that use a synthetic lethality approach targeting the reduced DNA damage repair conferred by mutant IDH using poly(adenosine 5′-diphosphate) ribose polymerase inhibitors (PARPis). The therapeutic effects are markedly enhanced by cotreatment with concurrent, localized radiation therapy. PARPi-buttressed multimodality therapies may represent a readily applicable approach that is selective for IDH-mutant tumor cells and has potential to improve outcomes in multiple cancers. - PARP inhibitor as a foundation of multimodality treatments is highly effective for IDH-mutant glioma and cholangiocarcinoma. - PARP inhibitor as a foundation of multimodality treatments is highly effective for IDH-mutant glioma and cholangiocarcinoma.
Gesehen am 04.06.2020